2020
DOI: 10.3389/fpsyg.2020.01732
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Awareness Multilevel Assessment Scale, a New Tool for the Assessment of Self-Awareness After Severe Acquired Brain Injury: Preliminary Findings

Abstract: Self-awareness (SA) is frequently impaired after severe acquired brain injury (sABI) and may lead to reduced subject’s compliance to treatment, worse functional outcome, and high caregiver distress. Considering the multifaceted nature of SA, a specific and effective assessment is crucial to address treatment of impairment of SA (ISA). Many tools can currently assess ISA; however, they have some important limits. In the present study, we proposed the Self-Awareness Multilevel Assessment Scale (SAMAS), a new sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…De plus, l'anosognosie même complique l'identification des risques par le professionnel, du fait de l'absence de consensus concernant sa définition, son évaluation et son évolution temporelle [29]. Actuellement, plusieurs échelles cliniques existent pour mesurer l'anosognosie, notamment la Self-Awareness Multilevel Assessment Scale (SAMAS) mesurant la conscience de soi à différents niveaux (déclaratif, émergent et anticipatif), avec la représentation du proche aidant [65] ; ou encore, l'échelle clinique Patient Competency Rating scale-neu-rorehabilitationImpaired self-awareness (PCRS-NR), récemment développée, qui mesure l'anosodiaphorie chez des patients ayant une lésion cérébrale grave [66]. Pour autant, même si les gériatres identifient adéquatement l'importance de l'anosognosie dans l'évaluation de l'aptitude au maintien à domicile, ils se réfèrent rarement aux échelles structurées du fait de l'hétérogénéité de celles-ci [67].…”
Section: Discussionunclassified
“…De plus, l'anosognosie même complique l'identification des risques par le professionnel, du fait de l'absence de consensus concernant sa définition, son évaluation et son évolution temporelle [29]. Actuellement, plusieurs échelles cliniques existent pour mesurer l'anosognosie, notamment la Self-Awareness Multilevel Assessment Scale (SAMAS) mesurant la conscience de soi à différents niveaux (déclaratif, émergent et anticipatif), avec la représentation du proche aidant [65] ; ou encore, l'échelle clinique Patient Competency Rating scale-neu-rorehabilitationImpaired self-awareness (PCRS-NR), récemment développée, qui mesure l'anosodiaphorie chez des patients ayant une lésion cérébrale grave [66]. Pour autant, même si les gériatres identifient adéquatement l'importance de l'anosognosie dans l'évaluation de l'aptitude au maintien à domicile, ils se réfèrent rarement aux échelles structurées du fait de l'hétérogénéité de celles-ci [67].…”
Section: Discussionunclassified
“…There were limited reports of self-awareness assessment use with clinicians reporting on clients' levels of self-awareness, task-specific challenges, and interventions for self-awareness. Research has shown that self-awareness assessments are important in order to assess and evaluate different components of a client’s self-awareness [ 38 ]. Additionally, components such as anticipatory awareness needs to be objectively assessed by a clinician [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that self-awareness assessments are important in order to assess and evaluate different components of a client’s self-awareness [ 38 ]. Additionally, components such as anticipatory awareness needs to be objectively assessed by a clinician [ 38 ]. In our study, less than 10% of clients were reported as receiving a self-awareness assessment.…”
Section: Discussionmentioning
confidence: 99%